Hostile Environments: Modifying Surfaces to Block Microbial Adhesion and Biofilm Formation - Derek Wilkinson; Libuše Váchová; Zdena Palková (Biomolecules)
Since the first observations of biofilm formation by microorganisms on various surfaces more than 50 years ago, it has been shown that most “unicellular” microorganisms prefer to grow in multicellular communities that often adhere to surfaces. The microbes in these communities adhere to each other, produce an extracellular matrix (ECM) that protects them from drugs, toxins and the host’s immune system, and they coordinate their development and differentiate into different forms via signaling molecules and nutrient gradients. Biofilms are a serious problem in industry, agriculture, the marine environment and human and animal health. Many researchers are therefore investigating ways to disrupt biofilm formation by killing microbes or disrupting adhesion to a surface, quorum sensing or ECM production. This review provides an overview of approaches to altering various surfaces through physical, chemical or biological modifications to reduce/prevent microbial cell adhesion and biofilm development and maintenance. It also discusses the advantages and disadvantages of each approach and the challenges faced by researchers in this field.